Pengaruh Brand Awareness, Viral Marketing, dan Metode Canvassing Terhadap Keputusan Pembelian Konsumen Nibras House Pasuruan - Nisak, Choirun; Nurhayati, Dies; Sobakh, Nurus (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
This research began with many consumers, especially in the Muslim fashion sector, who were confused about making purchasing decisions about products that suited their needs. Therefore, brand awareness, viral marketing, and canvassing methods can make consumers wiser in making purchasing decisions. This research aims to determine the influence of brand awareness, viral marketing, and the canvassing method on consumer purchasing decisions at Nibras House Pasuruan. This research uses quantitative descriptive methods. Research data was collected using questionnaires given to Nibras House Pasuruan consumers and observations made by researchers. The results of this research show that partially the calculated t value is greater than the t table value for the brand awareness, viral marketing and canvassing method variables, simultaneously the calculated F value is also greater than the F table. So brand awareness, viral marketing, and the canvassing method have a positive and significant influence partially and simultaneously on consumer purchasing decisions at Nibras House Pasuruan..